PLOS Neglected Tropical Diseases broadens its coverage of envenomings caused by animal bites and stings - Gutiérrez, José María (2021)
Animal envenomings, including those from snakes, scorpions, spiders, and other arthropods, are a major public health concern in developing countries, disproportionately affecting vulnerable populations. Snakebites alone cause millions of cases annually, with tens of thousands of deaths and many long-term sequelae. Scorpion stings, spider bites, and other envenomings can lead to severe systemic effects, particularly in children and rural communities with limited access to healthcare. These envenomings share characteristics with neglected tropical diseases, highlighting the need for epidemiological, clinical, therapeutic, and public health research to reduce their burden and improve medical management.